Organic compounds preserved in a 2.9 million year old stalagmite from the Nullarbor Plain, Australia - Blyth, Alison; Watson, J.; Woodhead, J.; Hellstrom, J. (Elsevier Science BV, 2010)
A 2.9 Ma stalagmite from the Nullarbor Plain, South Australia was analysed for organic components. In contrast to previously analysed stalagmites, no significant lipid record was recovered. However, qualitative TMAH thermochemolysis of the residual organic matter recovered a range of compounds, including a number of phenols previously associated with lignin. Comparison of this sample with a range of modern stalagmite samples from different environments indicated that the phenolic record in stalagmites can reflect the overlying vegetation regime, and has potential in investigating palaeoenvironmental change in this climatically important region.